2003
DOI: 10.1074/jbc.m309135200
|View full text |Cite
|
Sign up to set email alerts
|

GDP-Mannose 3′,5′-Epimerase Forms GDP-L-gulose, a Putative Intermediate for the de Novo Biosynthesis of Vitamin C in Plants

Abstract: Despite its importance for agriculture, bioindustry, and nutrition, the fundamental process of L-ascorbic acid (vitamin C) biosynthesis in plants is not completely elucidated, and little is known about its regulation. The recently identified GDP-Man 3,5-epimerase catalyzes a reversible epimerization of GDP-D-mannose that precedes the committed step in the biosynthesis of vitamin C, resulting in the hydrolysis of the highly energetic glycosyl-pyrophosphoryl linkage. Here, we characterize the native and recombin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
323
1
9

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 346 publications
(356 citation statements)
references
References 51 publications
6
323
1
9
Order By: Relevance
“…Pallanca and Smirnoff (24) have reported that the rate of AsA biosynthesis from D-[U- 14 C]glucose decreased linearly with the increase in the pool size of AsA in embryonic pea seedlings. In fact, L-Gal dehydrogenase and GME, which are in the D-Man/L-Gal pathway, were inhibited by AsA (9,25). These results suggest that the AsA level in plant cells is regulated at several steps by a feedback control.…”
mentioning
confidence: 63%
See 1 more Smart Citation
“…Pallanca and Smirnoff (24) have reported that the rate of AsA biosynthesis from D-[U- 14 C]glucose decreased linearly with the increase in the pool size of AsA in embryonic pea seedlings. In fact, L-Gal dehydrogenase and GME, which are in the D-Man/L-Gal pathway, were inhibited by AsA (9,25). These results suggest that the AsA level in plant cells is regulated at several steps by a feedback control.…”
mentioning
confidence: 63%
“…On incubation with 1 mM AsA, the GME of Arabidopsis plants was inhibited 15% (9). Recently, we have reported that L-Gal dehydrogenase activity was inhibited reversibly by AsA in a linearcompetitive manner (K i value of 133 M) (25).…”
Section: Discussionmentioning
confidence: 98%
“…13 and this study), we found that VTC5 displays a strong substrate preference for GDP-L-Gal and GDP-D-Glc over GDP-L-Fuc and GDP-D-Man and that UDP-DGlc, UDP-D-Gal, and ADP-D-Glc are not substrates at all. Furthermore, as for VTC2, VTC5 does not seem to phosphorolyze GDP-L-gulose, a compound formed, in addition to GDP-L-Gal, from GDP-D-Man by GDP-D-mannose 3Ј,5Ј-epimerase (25) in the reaction catalyzed upstream of GDP-L-Gal phosphorolysis in the Smirnoff-Wheeler pathway. Neither VTC2 nor VTC5 does, thus, seem to participate in the putative vitamin C synthesis pathway involving L-gulose and L-gulono-1,4-lactone formation, one of the alternative pathways that has been proposed for vitamin C synthesis in plants (25).…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, as for VTC2, VTC5 does not seem to phosphorolyze GDP-L-gulose, a compound formed, in addition to GDP-L-Gal, from GDP-D-Man by GDP-D-mannose 3Ј,5Ј-epimerase (25) in the reaction catalyzed upstream of GDP-L-Gal phosphorolysis in the Smirnoff-Wheeler pathway. Neither VTC2 nor VTC5 does, thus, seem to participate in the putative vitamin C synthesis pathway involving L-gulose and L-gulono-1,4-lactone formation, one of the alternative pathways that has been proposed for vitamin C synthesis in plants (25). Both VTC2 and VTC5 catalyze the phosphorolysis of GDP-L-Gal and GDP-D-Glc much more efficiently than the corresponding reverse reactions.…”
Section: Discussionmentioning
confidence: 99%
“…The biosynthesis of AsA proceeds via L-Gal (Wheeler et al, 1998), although conclusive evidence for all steps has only relatively recently become available (Conklin et al, 2006;Laing et al, 2007). Alternative biosynthetic routes involving uronic acids (Davey et al, 1999;Agius et al, 2003), L-gulose (Wolucka and Van Montagu, 2003), or myoinositol (Lorence et al, 2004) have been proposed in several plant species, including apple Razavi et al, 2005; Fig. 1), but their physiological relevance and contribution to the AsA pool is still far from clear in most plant species, with the possible exception of strawberry (Fragaria 3 ananassa; Agius et al, 2003;Cruz-Rus et al, 2011;Zorrilla-Fontanesi et al, 2011).…”
mentioning
confidence: 99%